Manioc 21: Releasing the potential of cassava - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
Cassava is a staple food in Central Africa, providing food security, jobs and income to millions of people. It also has enormous potential as an industrial crop, producing starch and high-quality flour that can substitute wheat in baking and for other uses. However, industrial demand is still limited. CTA’s project, Accelerating innovative and sustainable cassava business models for women and youth in Central Africa (Manioc21), is addressing this by supporting development of innovative business models that exploit this potential market.